Total Neoadjuvant Treatment for Rectal Cancer: Preliminary Experience. Issue 5 (May 2021) - Gilshtein, Hayim; Ghuman, Amandeep; Dawoud, Mirelle; Yellinek, Shlomo; Kent, Ilan; Sharp, Stephen P.; Nagarajan, Arun; Wexner, Steven D.
Introduction: Administration of chemotherapeutic regimens such as FOLFOX or CAPEOX with chemoradiation in the neoadjuvant setting, termed total neoadjuvant treatment (TNT), was introduced in recent years. By increasing the complete pathologic and clinical responses, patients with locally advanced rectal cancer may have better oncologic outcomes and potentially abstain from undergoing a proctectomy. Methods: All patients who underwent TNT at a single National Accreditation Program for Rectal Cancer accredited referral center were included. A retrospective analysis was performed using a computerized Institutional Review Board-approved database. Patient demographics, diagnostic workup, treatment regimens, and surgical and pathological reports were reviewed. Complete pathological response was the primary outcome. Univariable and multivariable logistic regression analyses were performed to identify potential factors predisposing to complete pathological response. Results: Thirty patients met the inclusion criteria, 14(46.6%) of whom had complete pathologic response. There was no difference in baseline demographic characteristics between patients who achieved complete pathological response and those who did not. Pathology revealed a 92% intact mesorectum rate in the complete pathologic response group and a mean of 24 harvested lymph nodes in the entire study cohort. Both univariable and multivariable logistic regression analyses failed to demonstrate statistically significant factors predicting complete pathologic response, magnetic resonance imaging (MRI) tumor size, and posttreatment MRI lymph node positivity. Conclusion: TNT is safe and efficient for patients with locally advanced rectal cancer. It increases complete pathological and clinical response rates and may more widely evolve to be the treatment of choice in this group of patients in the near future.